2021
DOI: 10.1021/acsnano.0c09228
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Perovskite Quantum Dots Modified by Europium Complex for Dual-Responsive Optical Encoding

Abstract: Inorganic perovskite quantum dots (QDs) have attracted great scientific attention in the field of luminescent materials, but the application has been limited by the inferior stability that results from highly dynamic capping ligands. In this work, we use a rare-earth complex to modify perovskite QDs with ligand exchange to realize perovskite functionalization; meanwhile, the stability of perovskite QDs is greatly improved. Density functional theory calculation results show that the adsorption energy of the eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…44–47 In past decades, many types of white light materials were reported, such as organic polymers, metal-doped inorganic materials, small organic molecules, quantum dots and nanocrystals, as well as metal complexes. 48–50 For white emission lanthanide coordination polymer materials, the white emission is often obtained by adjusting the ratio of the three primary colors of red, green and blue originating from the emissions characteristic of Tb 3+ , Eu 3+ and the organic ligand either by a co-doping strategy or by tuning the excitation wavelength or temperature. 51 As is well known, it is easy to achieve the color-tuning behaviors of lanthanide complexes through changing the type and proportion of the Ln 3+ ion, yet this method may result in a considerable waste of rare earth resources.…”
Section: Resultsmentioning
confidence: 99%
“…44–47 In past decades, many types of white light materials were reported, such as organic polymers, metal-doped inorganic materials, small organic molecules, quantum dots and nanocrystals, as well as metal complexes. 48–50 For white emission lanthanide coordination polymer materials, the white emission is often obtained by adjusting the ratio of the three primary colors of red, green and blue originating from the emissions characteristic of Tb 3+ , Eu 3+ and the organic ligand either by a co-doping strategy or by tuning the excitation wavelength or temperature. 51 As is well known, it is easy to achieve the color-tuning behaviors of lanthanide complexes through changing the type and proportion of the Ln 3+ ion, yet this method may result in a considerable waste of rare earth resources.…”
Section: Resultsmentioning
confidence: 99%
“…1b). [39][40][41][42][43] Compared with pure Eu(DBM) 3 Áphen, NH 2 -MSNs@Eu(DBM) 3 Áphen had a longer luminescence lifetime and lower quantum yield (Fig. S4 and Table S1, ESI †), and the reduction in quantum yield should be mostly attributed to the scattering and absorption losses of SiO 2 nanopowders, which can absorb and disperse the excitation light into the non-radiative processes.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the fluorescence transitions switch between different states based on external factors such as temperature, dopant ions and their concentration, etc. Feng et al 198 reported a novel approach to modeling optical encoding materials using europium complex-decorated CsPbBr 3 quantum dots with highly stable dual-stimuli-response. The schematic illustration of the formation of the europium complex Eu(PBA) 3 AA (HPBA = N-(2pyridinyl)benzoylacetamide, AA = 8-aminooctanoic acid)-decorated CsPbBr 3 quantum dots is shown in Fig.…”
Section: Emerging Application In Optical Encodingmentioning
confidence: 99%